Robotic-assisted thoracoscopic right upper lobe sleeve resection - Huang, Jia; Li, Chongwu; Jiang, Long; Lin, Hao; Lu, Peiji; Li, Jiantao; Luo, Qingquan (Journal of Thoracic Disease, 2018)
Sleeve lobectomy is indicated for centrally located lung cancer as an alternative to pneumonectomy. It has mainly been performed by thoracotomy because of the complexity of airway reconstruction. With new technical advances and more experience gained in video-assisted thoracic surgery (VATS), sleeve lobectomy performed by VATS has been reported, but its suitability is limited by its lack of depth perception and maneuverability.